A critical review of global vegetable benchmarking - Jackson, Elizabeth (2019)
The aim of this research was to conduct a critical investigation of global vegetables benchmarking initiatives for the development of a new benchmarking system for vegetable production in Western Australia. While farm-level benchmarking is far more robust for arable crop production and livestock enterprises, the rigorous benchmarking systems from non-government organisations were found to be the Farm Business Survey in the UK, Zentrum für Betriebswirtschaft im Gartenbau e.V. in Germany, AACREA in Argentina, Farm Digital in the Netherlands for innovative data sharing platforms, Agribenchmark benchmarks international farm-level data and Farm Sustainability Assessment which is based in the USA but collects global farm data. It was found that databases are similarly structured and principally based on gross margin analyses with additional information provided on fixed costs. Overall, the data that are provided are relatively standard: income/receipts from sales and the costs of various fixed and variable costs. Most benchmarking reports also provide details of yields in different formats. The final recommendation of this research is for those building a new vegetables production benchmark to also consider large-scale producers about the possibility of sharing benchmarking data.